Comparative Assessment of Hemodynamics in Cardiosurgical Patients - I. P. Nikolayeva; G. A. Livanov; I. S. Kurapeyev; V. G, Pokrovsky; Yu. I. Pitenin; L. D. Tsvetnova; N. Yu. Volkov; A. N. Lodyagin (Общая реаниматология)
The results of comparative determination of the values of stroke volume (SV) and cardiac index measured by integral rheography (IRG) after M. I. Tishchenko, thermodilution (using a Swan-Ganz catheter), and echocardiography (EchoCG) were studied in 139 patients with acquired heart diseases (AHD) and coronary heart disease (CHD) in different periods after cardiosurgical operations under extracorporeal circulation. The reasons for lowering SV measured by rheography were revealed. The changes in the oscillations of terminal circulatory vessels, which are associated with altered ejection fraction and decreased capillary blood flow velocity pulse under the action of different doses of adrenaline, were shown to affect the genesis of rheograms. The problem in assessing the nature of blood flow (pulsation) in the terminal portion of the circulatory system in emergency medicine is discussed.